Engineering of Yeast for the Production of Fuels and Polyketides - Choi, Jin Wook (eScholarship, University of California, 2014)
Saccharomyces cerevisiae is a promising microorganism for the production of ethanol for fuel, and the synthesis of precursors to industrial chemicals and natural products. The goal of this research was to engineer S. cerevisiae strains for the enhanced synthesis of these products. For the economical production of bioethanol, complete use of hemicellulosic sugars is necessary. Thus, the fungal arabinose pathway was imported and evaluated. The NADH-dependent L-xylulose reductase (ALX1) from Ambrosiozyma monospora was introduced to balance the use of redox cofactors. Three fungal arabinose pathway genes ( XYL1 , lad1 , and lxr1 or ALX1 ) were codon and codon pair optimized for expression in S. cerevisiae . Various combinations and copy numbers of the three required genes were evaluated by measuring growth and xylitol production; use of ALX1 resulted in up to 9-fold higher xylitol titers relative to LXR1. Arabinose uptake, the rate-limiting step for arabinose utilization in S. cerevisiae , was also addressed by creating a chimeric protein of Gal2 and Hxt1. Polyketides are versatile molecules that can be industrial chemical precursors as well as drug precursors. Five different thioesterases were compared for the release of dihydromonacolin L (DML), the precursor to the cholesterol lowering agent lovastatin, from LovB in S. cerevisiae, and AptB was identified to be the best candidate. Most polyketides use acetate as starter unit and malonate or other malonate-based molecules as extender units. 6-methylsalicylic acid synthase (6-MSAS) was chosen as the model system for the engineering of S. cerevisiae to increase the intracellular availability of acetate and malonate. 6-MSA titer showed improvement by 50% via deletion of PYC1 , by 3-fold via engineering of Acc1 (9-fold in activity), and by 90% via combined use of N-degron tagged URA3 and autoselection for the expression of 6-MSAS in complex medium. The strategies developed in this research contribute to the metabolic engineering of S. cerevisiae for the synthesis of ethanol, and biochemical and drug precursors.